Global vaccine action plan lessons learned I: Recommendations for the next decade. Issue 33 (14th July 2020) - MacDonald, Noni; Mohsni, Ezzeddine; Al-Mazrou, Yagob; Kim Andrus, Jon; Arora, Narendra; Elden, Susan; Madrid, Marie-Yvette; Martin, Rebecca; Mahmoud Mustafa, Amani; Rees, Helen; Salisbury, David; Zhao, Qinjian; et al.
Highlights: GVAP provided a comprehensive and coherent global framework for immunization. Much progress was achieved under GVAP, although most GVAP goals will not be met. GVAP was perceived as top-down, with too little consideration of country context. GVAP was only partially implemented, and it had limited levers to influence country actions. Many targets were seen as unrealistic, particularly in the absence of additional funding. Lessons learned from GVAP can inform the Immunization Agenda 2030. Abstract: The Global Vaccine Action Plan 2011–2020 (GVAP) was developed to realize the ambitions of the Decade of Vaccines – that all individuals and communities enjoy lives free from vaccine-preventable diseases. It included a comprehensive monitoring and evaluation/accountability framework to assess progress towards global targets with recommendations for corrective actions. While many of the GVAP targets are very unlikely to be met by the end of 2020, substantial progress has nevertheless been made, establishing a strong foundation for a successor global immunization strategy, the Immunization Agenda 2030 (IA2030). The Strategic Advisory Group of Experts on immunization has made a series of recommendations to ensure that the lessons learned from GVAP inform the development and implementation of IA2030.